The effect of Quebec's CEGEPs on total years of schooling - Pierre Fortin; Natalia Mishagina (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
We study the effects of the CEGEP innovation of the late 1960s in the province of Quebec on total years of schooling based on a difference-in-difference methodology applied to the microdata from the 20% sample of the 2001 Canadian Census long form. Eight demographic groups are investigated, namely Francophone men and women from Montreal, Quebec City and "Rest-of- Quebec", and Montreal Anglophones of each gender. The average estimated effects are statistically positive and large: 0.33 year for men and 0.41 year for women. Putting these results in context, we further argue that they likely underestimate the true behavioural effects of the reform on educational attainment, particularly in the case of Francophones.
Keywords: I23; I28; 330; college; CEGEP; Quebec; schooling